Rex - Dubosarsky, Ursula, 1961-; Mackintosh, David, 1966- (Scholastic, 2006)
Students take turns bringing home the class chameleon and writing about how he spent his visit.
First published: Australia : The Penguin Group.
"A Neal Porter book."
1.7
K-3
Keywords: Chameleons as pets -- Juvenile fiction; Schools -- Juvenile fiction; Chameleons as pets -- Fiction; Pets -- Fiction; Schools -- Fiction; Chameleons -- Fiction; Pets -- Fiction; School stories